A prediction of cell differentiation and proliferation within a collagen-glycosaminoglycan scaffold subjected to mechanical strain and perfusive fluid flow. - O'BRIEN, FERGAL (My University, 2010)
Mesenchymal stem cell (MSC) differentiation can be influenced by biophysical stimuli imparted by the host scaffold. Yet, causal relationships linking scaffold strain magnitudes and inlet fluid velocities to specific cell responses are thus far underdeveloped. This investigation attempted to simulate cell responses in a collagen-glycosaminoglycan (CG) scaffold within a bioreactor. CG scaffold deformation was simulated using mu-computed tomography (CT) and an in-house finite element solver (FEEBE/linear). Similarly, the internal fluid velocities were simulated using the afore-mentioned mu CT dataset with a computational fluid dynamics solver (ANSYS/CFX). From the ensuing cell-level mechanics, albeit octahedral shear strain or fluid velocity, the proliferation and differentiation of the representative cells were predicted from deterministic functions. Cell proliferation patterns concurred with previous experiments. MSC differentiation was dependent on the level of CG scaffold strain and the inlet fluid velocity. Furthermore, MSC differentiation patterns indicated that specific combinations of scaffold strains and inlet fluid flows cause phenotype assemblies dominated by single cell types. Further to typical laboratory procedures, this predictive methodology demonstrated loading-specific differentiation lineages and proliferation patterns. It is hoped these results will enhance in-vitro tissue engineering procedures by providing a platform from which the scaffold loading applications can be tailored to suit the desired tissue. (C) 2009 Elsevier Ltd. All rights reserved.
PUBLISHED
Keywords: Bioengineering; TISSUE-ENGINEERING SCAFFOLDS